2017
DOI: 10.1007/s41465-017-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancement and Coping in an Australian University Student Sample

Abstract: Cognitive enhancement (CE) agents are those purported to improve or augment aspects of cognition such as working memory, creativity, and executive function in healthy individuals. CE by university students looking to improve their academic performance, particularly through the use of pharmacological agents (or nootropics), has become an area of increasing interest for researchers. However, studies on the prevalence of, and motivations behind, students' CE use at Australian universities are limited. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 42 publications
2
25
1
Order By: Relevance
“…Although alcohol and marijuana are rarely used for the purpose of neuroenhancement (4) [e.g. 5.1% and 1.8% prevalence rates among Swiss students (4), and 3.8% and 1.0% among Australian students (10), respectively], in our study a high increase in alcohol (24.8%) and marijuana (19.0%) consumption during the week before an exam was found. Neither alcohol nor marijuana consumption was correlated with exam anxiety, which was also found in a study of German medical students (25).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Although alcohol and marijuana are rarely used for the purpose of neuroenhancement (4) [e.g. 5.1% and 1.8% prevalence rates among Swiss students (4), and 3.8% and 1.0% among Australian students (10), respectively], in our study a high increase in alcohol (24.8%) and marijuana (19.0%) consumption during the week before an exam was found. Neither alcohol nor marijuana consumption was correlated with exam anxiety, which was also found in a study of German medical students (25).…”
Section: Discussioncontrasting
confidence: 50%
“…None of our students reported the use of prescription or illicit psycostimulants compared to the prevalence in other countries mentioned earlier (4,8,(10)(11)(12)(13)31). Although these comparisons should be considered with caution because our study included only first-year students, the study of medical students in the US also showed psychostimulant non-users to be more likely to be first year students or to grow up outside of the US (32).…”
Section: Discussionmentioning
confidence: 50%
“…Riddell et al study's findings cleared the current understanding of drug usage in Australia and contextualized possible ways of intervening in university (students) health and opportunities for regulating. In particular, helping students to manage stress at a considerable level may be helpful by identifying less-harmful methods (26). The results of Sattler et al study showed that students tended to enhance their cognitive performance by drugs compared to university teachers; however, the overall willingness was low (27).…”
Section: Discussionmentioning
confidence: 99%
“…Others may use different coping methods with the intention of maintaining high performance levels. This can be done by managing the demands (e.g., busy schedules) to reduce the associated costs of the extra effort (e.g., mental capacity) or to counteract strain and its negative consequences (Maier et al, 2015;Riddell et al, 2018;Wolff et al, 2014). Using NMUPD-CE drugs with the perceived possibility of increasing or maintaining alertness, concentration, and wakefulness are such coping methods.…”
Section: A Modified Job Demands-resources Model To Understand the Nonmedical Use Of Prescription Drugs For Cognitive Enhancementmentioning
confidence: 99%